2011
DOI: 10.1002/kpm.377
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Process Ownership and Line Management in a Matrix-like Organization

Abstract: Organizations are traditionally designed through the vertical structuring of units in a hierarchy. Business Process Management challenges this approach, and emphasizes horizontal work processes that cut across hierarchical units and competence areas. Few studies have analyzed what happens when the hierarchy is confronted by the mechanisms set up to manage business processes. Here, based on a case study, we describe and analyze the relation between a process owner (a key role in Business Process Management) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 17 publications
2
49
0
1
Order By: Relevance
“…The human factor is essential in the position of a process owner. The integral part of his work is also ensuring the right resources and responsibility matrix for activities and competence development (Nesheim, 2011). The empirical research of Kohlbacher and Gruenwald (2011) confirmed that organizations which appointed process owners and delegated them with process performance measurement reached higher performance than organizations which implemented only one of these components.…”
Section: Definition Of the Process And Process Typologymentioning
confidence: 86%
See 1 more Smart Citation
“…The human factor is essential in the position of a process owner. The integral part of his work is also ensuring the right resources and responsibility matrix for activities and competence development (Nesheim, 2011). The empirical research of Kohlbacher and Gruenwald (2011) confirmed that organizations which appointed process owners and delegated them with process performance measurement reached higher performance than organizations which implemented only one of these components.…”
Section: Definition Of the Process And Process Typologymentioning
confidence: 86%
“…Many other authors agree with this statement, too (Nesheim, 2011). They claim that process approach is based on the assertion that the cause of poor economic results resides in inefficient ongoing processes in the company.…”
Section: Theoretical Background -Bussines Process Managementmentioning
confidence: 98%
“…In the conclusion of a quantitative study in the financial services industry the importance of BPM in driving customer satisfaction is emphasised (Kumar et al, 2008). Process changes also impact the design of organizations (Nesheim, 2011) which must be prepared for cultural change (Smart et al, 2009). Such change must be addressed from a process perspective and properly governed.…”
Section: Discussion Of Process Owner Competenciesmentioning
confidence: 99%
“…In prior studies, interpersonal skills have been found to be significant and although competence and trust in process owners were deemed to be high, communication skills were ranked moderately lower. Consequently, it was recommended that process owners communicate and engage in real dialogues that build relationships (Nesheim, 2011).…”
Section: Discussion Of Process Owner Competenciesmentioning
confidence: 99%
See 1 more Smart Citation